Single-cell transcriptomic profiling of dorsal root ganglion: an overview - Keyu Xie; Keyu Xie; Xu Cheng; Tao Zhu; Donghang Zhang (Frontiers Media S.A., 2023)
The somatosensory neurons in the dorsal root ganglion (DRG) are responsible to detect peripheral physical and noxious stimuli, and then transmit these inputs into the central nervous system. DRG neurons are composed of various subpopulations, which are suggested to respond to different stimuli, such as mechanical, thermal, and cold perception. For a long time, DRG neurons were classified based on anatomical criteria. Recently, single-cell (scRNA-seq) and single-nucleus RNA-sequencing (snRNA-seq) has advanced our understanding of the composition and functional heterogeneity of both human and rodent DRG neurons at single-cell resolution. In this review, we summarized the current literature regarding single-cell transcriptomic profiling of DRG to provide an integral understanding in the molecular transcriptomes, cell types, and functional annotations of DRG neurons in humans and rodents.